Implementasi Program Bantuan Langsung Tunai (BLT) Lansia Kecamatan Bintan Utara Kabupaten Bintan - Zhahara Dwi Amanda; Nur Asmalaturrahmah Dwi Putri; Uly Sophia (CV. ITTC INDONESIA, 2026)
The increasing number of elderly people in Bintan Regency has encouraged the Bintan Regency Government to implement the Direct Cash Assistance (BLT) Program for the Elderly, funded by the Regional Budget (APBD). In North Bintan District, there are 2,080 elderly people, but only 772 people (37%) received assistance, so the program's implementation needs to be reviewed. This study aims to analyze the implementation of the BLT Program for the Elderly in North Bintan District and identify supporting and inhibiting factors. The study used a qualitative method with a descriptive approach through in-depth interviews with 15 informants. The results show that the implementation of the BLT Program for the Elderly based on the six Van Meter and Van Horn indicators has been running quite well, but has not been optimal due to constraints in data updating, limited resources, and information delivery. Supporting factors include coordination between implementers, utilization of SIKS-NG and DTKS, and commitment of the apparatus. Therefore, regular data updates, increased coordination, capacity of assistants, and information delivery are needed to make the program more optimal, on target, and sustainable.